Paraguay : Staff Report for the 2004 Article IV Consultation and Second Review Under the Stand-By Arrangement and Requests for Waiver and Modifications of Performance Criteria. (IMF Staff Country Reports; Country Report, 2005)
This paper examines Paraguay's 2004 Article IV Consultation and Second Review Under the Stand-By Arrangement and Requests for Waiver and Modifications of Performance Criteria. Paraguay's economy has stabilized in 2004, but growth remains modest. A late season drought depressed output of soy, the largest export crop, reducing expected agricultural output growth to near zero, but non-agricultural output is recovering. The guarani has strengthened by 4 percent against the U.S. dollar so far in 2004. The fiscal situation has improved markedly since the new government took office in August 2003.